Age, rehabilitation and surgery characteristics are re-injury risk factors for adolescents following anterior cruciate ligament reconstruction - Law, Mallory A.; Ko, Yi-An; Miller, Ashley L.; Lauterbach, Kristin N.; Hendley, Christopher L.; Johnson, Julie E.; Tsai, Liang-Ching (Physical therapy in sport, 2021)
To examine the effect of age on post-ACLR rehabilitative outcomes and identify surgical/rehabilitative characteristics as ACL re-injury risk factors in adolescents. Cohort study. Children’s hospital. 273 adolescents with first-time ACLR. Demographics, injury history, surgery, and outcomes documented during post-ACLR physical therapy (PT) sessions were extracted from medical records. Effects of age on outcomes were examined using multivariate regression. ACL re-injury risk factors were identified using survival analysis with Cox regression. Re-injury was recorded in 47 patients (17.2%) with a median follow-up time of 3.1 years and median re-injury time of 13.4 months post-surgery. Younger age (Hazard-Ratio, HR = 1.264 per year decrease; P = 0.005), receiving surgery within 1 month post-injury (HR = 3.378 vs. >3 months; P = 0.012), starting PT within 3 days post-surgery (HR = 3.068; P = 0.022), and decreased number of PT sessions (HR = 1.118 per 3-session decrease; P = 0.010) increased re-injury risk. Although age was associated with re-injury risk, age was not associated with any outcome (P > 0.059). Adolescents who are younger, receive surgery and post-surgery PT sooner, or attend fewer PT sessions may be at an increased re-injury risk. Younger patients achieved similar outcomes despite elevated re-injury risk. Current discharge criteria are inadequate in identifying high re-injury risk patients. •Adolescent patients who are younger had a higher ACL re-injury risk.•However, similar rehabilitative outcomes and progression across all youth patients.•Need sensitive discharge criteria to identity high re-injury risk youth patients.•Getting ACLR or PT sooner or attending less PT also led to a higher re-injury risk.•Structured rehabilitation/PT post-ACLR is critical in preventing ACL re-injury.